Folk Medicine Of Alter Do Chão, Pará, Brazil - Branch, Lyn C.; Silva, Marlene Freitas da (Acta Amazonica, 1983)
A total of 192 medicinal plants were collected in Alter do Chão, Pará. Reliable informants living in the area described 394 medicinal preparations made from these plants and used for various sicknesses, as showm in Table 1. More than 52% of the medicinal species are collected from the native forests and many are also used as food sources.